A case involving laparoscopic decortication of a large simple renal cyst using conventional monopolar device. (March 2022) - Kobayashi, Kota; Yoneyama, Shuko; Iwasa, Eren; Karibe, Jurii; Yamashita, Daisuke; Takizawa, Akitoshi
Abstract: Introduction and importance: Simple renal cysts are common in adults, but most of them are asymptomatic. Usually, percutaneous puncture is an initial treatment, but laparoscopic decortication may be effective for recurrent simple renal cyst. Herein, we report a case in which a large symptomatic simple renal cyst was treated with laparoscopic decortication using conventional monopolar device. Case presentation: A 34-year-old female visited our hospital with chief complaints of back pain and abdominal fullness. Computed tomography showed a right simple renal cyst (diameter: 140 mm). We performed percutaneous drainage with sclerotherapy, but the cyst recurred a month later. Thus, we carried out laparoscopic decortication. We opened the cyst wall via a retroperitoneal approach and trimmed it using monopolar scissors. The operation time was 124 min. The patient's postoperative course was uneventful, and no complications were observed. Following surgery, the patient was asymptomatic. Clinical discussion: In our case, we performed operation using a conventional monopolar device without sealing devices. It has been reported that the use of sealing devices can make laparoscopic surgery safer and reduce the operation time, but we herein report that laparoscopic decortication with a conventional monopolar device is an effective and safe treatment option for symptomatic simple renal cysts and that more expensive energy sources are not required. Conclusion: We successfully performed laparoscopic decortication of a large symptomatic simple renal cyst. This operation is minimally invasive and safe. Highlights: Simple renal cyst are common and most cases are asymptomatic, but large simple renal cyst may cause symptoms such as pain. As an initial treatment, percutaneous puncture is widely performed, but recurrence rates are high. Laparoscopic decortication may be an effective and safe treatment option for large symptomatic simple renal cysts.